Ecos do labirinto : Hugo Chávez e a reconstrução da mítica bolivariana na Venezuela (1999-2009) - Reis, Thiago Menini dos (2010)
This research wants to analyze President Hugo Chavez public image starting from the association with the liberator Simon Bolivar and his symbolic representation. Hugo Chavez started building his public image on the 4 of February with his declaration on a national TV channel just after being arrested with others soldiers during a military insurrection. During his first speech, Hugo Chavez managed to obtain the support of most Venezuelan citizens by associating himself to Simon Bolivar. After this, Hugo Chavez increased his power within Venezuelan politics and in 1998 became President of Venezuela. Since then Hugo Chavez promoted many reforms based on the “Bolivar doctrine”, this doctrine had a strategic role reviving Bolivar political myth, one of the most efficient tool used by Chavez to keep the power. Liberator Bolivar myth has been used several times by politicians of different times and for many purposes. This research wants to underline the main aspects of Hugo Chaves appropriation of Simon Bolivar myth by discussing the importance of this myth within Venezuelan politics. Different types of sources have been selected: first of all Hugo Chavez and Bolivarian Revolution biographies, then Hugo Chaves public speeches published by the official Venezuelan press, selected for their advertising purposing.